Effectiveness of Management Practices at the Techo Sen National Polytechnic Institute, Cambodia (2018–2023) - Chroeng , Nary; Son, Oudom; Ros, Ravuth (Journal of Applied Research and Innovation (JARI), 2026)
This study examined the effectiveness of management practices at the Techo Sen National Polytechnic Institute, located in Kandal, Cambodia, within context of Technical and Vocational Education and Training (TVET) in Southeast Asia. With this study design, the theoretical research design was used. Secondary data analysis and SWOT frameworks were carried out in presenting the results. Findings revealed that the institute demonstrated strong alignment with national TVET policies, effective leadership, and comprehensive capacity-building initiatives. The key challenges included limited financial and physical resources, infrastructure constraints, and gaps between curricula and labor market demands. The study provided practical implications to strengthen governance, optimize resource utilization, and improve program relevance, offering the insights for policymakers, educational administrators, and development partners. By situating Cambodia’s experience within regional TVET landscape, the research contributes to understanding how Southeast Asian polytechnic institutions enhance management effectiveness and workforce readiness in resource-constrained contexts.